Care pathway analysis and evidence gaps in adult-onset Still’s disease: interviews with experts from the UK, France, Italy, and Germany - Ursini, Francesco; Gregg, Emily; Canon-Garcia, Viviam; Rabijns, Hilde; Toennessen, Katrin; Bartlett, Kaz; Graziadio, Sara (Frontiers in Medicine, 2023)
Adult-onset Still's disease (AOSD) is a rare systemic inflammatory disease of unknown etiology. Published AOSD data are limited, and clinical guidelines were lacking until recently. Managing AOSD remains largely empirical with uncertainties and high variability about the optimal care pathway. Therefore, we used a qualitative approach to collect clinical judgements from the UK, Italy, France and Germany to inform the development of an agreed care pathway. Our work aimed to decrease the uncertainty associated with clinical practice, inform future research in AOSD, and help identify standardized definitions and outcomes in this population. Semi-structured interviews and thematic analysis were conducted.Eleven clinicians were interviewed between May and July 2022: four were based in Italy, three in the UK, two in France, and two in Germany. In this work, we identified the structure of the typical care pathway for AOSD patients, which can be used to inform future economic models in AOSD. The general structure of the pathway was similar across countries. Non-steroidal anti-inflammatory drugs are prescribed during the diagnostic workup while an additive approach is commonly used in confirmed cases: corticosteroids, conventional synthetic disease-modifying antirheumatic drugs, then biologic disease-modifying antirheumatic drugs (bDMARDs) (dose increased before switching). For severe presentations, more aggressive approaches with higher doses and early use of bDMARDs are used. The main elements of variation among countries and clinicians were the criteria used for diagnosis; order of bDMARDs and preferential treatments for articular and systemic patients; and tests for patient monitoring. There is also a lack of standardized outcome measures making comparisons and evidence synthesis challenging.We identified important evidence gaps for clinical practice, e.g. reliable tests or scores predictive of disease progression and treatment outcome, and recommendations for research, e.g. reporting of compliance rates and use of the Yamaguchi criteria for clinical study inclusion. Consensus is needed around the use of the Systemic score in clinical practice and the clinical utility of this score. A standardized definition of remission is also required in AOSD, and further research should look to identify and validate the specific laboratory markers to be considered when assessing remission.